2022
DOI: 10.1098/rsos.221349
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of reactive oxygen species scavenging pathways of norbergenin utilizing DFT approaches

Abstract: Bergenin is a polyphenolic compound that contains isocoumarin skeletal derived from C -glycosylated 4- O -methylgallic acid. The biological activities of this compound and its derivatives are quite diverse. Recent studies reveal neuroprotective effects in vitro and in vivo in Alzheimer's. Norbergenin is a demethylated form of bergenin, known for better antioxidant capacity and associated with neuroprotective propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…The Eyringpy program was utilized to acquire the tunneling transmission coefficient ( κ ), as done by prior works. 44,68–71 For any scavenging mechanism that involved electron transfer, such as SET and SPLET, Marcus theory (eqn (6)) was performed to find their activation energy . 72,73 …”
Section: Theoretical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Eyringpy program was utilized to acquire the tunneling transmission coefficient ( κ ), as done by prior works. 44,68–71 For any scavenging mechanism that involved electron transfer, such as SET and SPLET, Marcus theory (eqn (6)) was performed to find their activation energy . 72,73 …”
Section: Theoretical Methodsmentioning
confidence: 99%
“…From our previous research, one observed phenomenon is the predominance of the HT (hydrogen transfer) mechanism by phenolic groups in antioxidant compound. 44 Meanwhile, other fragments, such as benzyl groups, exhibit higher activation energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…were also found, such as norbergenin, 11-O-acetyl bergenin and 11-O-caffeoylbergenin isolated from the leaves of F. virosa, together with flavonoid glycosides (e.g., kaempferol 3-O-(4-galloyl)-β-D-glucopyranoside) and phenolic derivatives [110,136,137]. Among these products, the demethoxylated form of bergenin, which is known as norbergenin (Figure 3a), is a potent inhibitor of oxidative stress, acting as an efficient scavenger for oxygen-based radicals [138] and a potent anti-inflammatory agent [139].…”
Section: Derivativesmentioning
confidence: 99%
“…It reacts with most biomolecules at diffusion-controlled rates (k > 10 9 M −1 s −1 ). Due to its high reactivity, its half-life is extremely short (10 −9 s) [81].…”
Section: Hydroxyl Radical and Dna Damagementioning
confidence: 99%